MUSLIM CUSTOMER BEHAVIOR IN HALAL FOOD ONLINE PURCHASING - Hasan Al-Banna (Journal of Islamic Monetary Economics and Finance, 2019)
To meet the global population needs, it is projected at least eighty billion dollars in investment per year to support the food security until 2050. Arguably, the agriculture financing growth has stalled due to many reasons, while Islamic finance has the potential to spur the growth of agriculture financing to promote global food security. Meanwhile, agriculture in Indonesia is still nowhere to its potential. It is hindered by an inefficient and underdeveloped downstream segment, low access to financial and technology. This is a huge opportunity for Islamic finance in helping to bridge the gap through value chain financing approach as one of the strategies to reduce risk and provide socio-economic spillover effect along the chain. Islamic finance could promote agricultures sustainability and a more efficient process with FinTech enabled platform. The multiple case studies propose a sharia compliant community-based financing model in agricultural value chain practice with FinTech enabled platform. The result is this model integrating all actors from different market segmentation, including landowners, suppliers, farmers, brokers, retailers, and investors into an Islamic value chain-financing platform. However, determining buying intention, partnership establishment, and technology infrastructure are pivotal for its future implementation.